The Role of Perum Perhutani Independent Business Unit Facilitator in Tourism Development of Putuk Truno Prigen Waterfall - Alisyafir Rohmah; Ilmi Usrotin Choiriyah (Indonesian Journal of Public Policy Review, 2022)
Tourism is a variety of tourism activities that are supported by various facilities and services provided by the community, entrepreneurs, government and local governments. One of the tourism objects in Pasuruan Regency managed by Perhutani is Putuk Truno Waterfall. Putuk Truno Waterfall is one of the Perhutani areas under the Ecotourism Independent Business Unit division. This study aims to understand the role of the facilitator of the Perum Perhutani Independent Business Unit in the Tourism Development of Putuk Truno Prigen Pasuruan. This research method uses descriptive qualitative method. Qualitative data analysis techniques were obtained through interviews, observation and documentation. The results of the research on the role of the Perum Perhutani Independent Business Unit Facilitator in the Tourism Development of Putuk Truno Prigen Pasuruan Waterfall is to carry out the role as a facilitator by providing physical and non-physical facilities. Keywords – , , .